L-asparaginase Activity in Growing Conditions of Streptomyces spp. associated with Therapon jarbua and Villorita cyprinoids of Veli Lake, South India - Dhevendaran, Kandasamy; Y.K., Anithakumari (Fishery Technology, 2025)
Streptomyces spp. isolated from the gut of fish, Therapon jarbua and shellfish, Villorita cyprinoids exhibited L-asparaginase activity under growing conditions in a liquid broth. Streptomyces AQBTJ 60 (isolate from fish) showed maximum enzyme activity at pH 8.0 whereas Streptomyces AQB VC67 showed it at pH 7.0. They showed optimum enzyme activity and growth at temperature 370C. Carbon sources and amino acids had varying influence based on the constituents in the gut or viscera of the host organisms and heavy metals inhibited activity and growth. Similar trend was noticed with sodium chloride in the estuarine strains.